EFEKTIVITAS MODIFIKASI BUBU DASAR KONSTRUKSI ATRAKTOR TERHADAP HASIL TANGKAPAN IKAN DI PERAIRAN PULAU LEMUKUTAN - Ho Putra Setiawan; Sadri Sadri; Agus Setiawan; Slamet Tarno (Fakultas Perikanan dan Ilmu Kelautan, 2019)
Trap have different construction to catch the fishes. The purpose of this study is to obtain the basic trap construction model method, analyze the effectiveness of basic construction modifications and financial analysis. The acquisition of catch composition shows that red snapper (Lutjanus alfifrotouris) gets the largest proportion in unit weight (kg) at a depth of 10 m for modification of basic trap attractors construction beam model of 27,49% and construction does not use attractors at 16,45% and at the depth of 14 m for modification of the base trap attractor construction beam model is 27,40% and the construction does not use attractors at 24,97%, while the largest proportion in units of number (tail) at a depth of 10 m yellow tail fish (Caesio erythrogaster) is 37,89% while construction beam models do not use attractors at 22,80% and at 14 m depth the largest proportion obtained in units of number (tail) is found in yellow tail fish (Caesio erythrogaster) for modification of the base trap attractor construction beam model of 25,64% while the construction does not use contractor at 19,94%. The diversity index value (H') of Lemukutan Island waters region is 3,9 while the comparative analysis of fish production (one-way anova) shows that the treatment of the two fishing gear construction models did not significantly affect the production of fish caught at a depth of 10 m and 14 m. The results of the R/C ratio showed that the modified fishing gear of the attractor construction beam model obtained an R/C = 1,435 and the construction did not use the attractor R/C value = 1,031, thus the two basic construction models were economically feasible to develop as a business arrest in Lemukutan Island waters.